Minimum wage and spillover effects in a minimum wage society - Sefil-Tansever, Sinem; Yilmaz, Ensar (WILEY, 2024)
Minimum wage policies are widely implemented in developing countries, but their consequences remain uncertain. This study empirically investigates the impact of the minimum wage on monthly income inequality and its spillover effects in Turkey between 2004 and 2022, utilizing comprehensive micro data. We aim to shed light on the impact of national minimum wage policies by examining their diverse influences on the wage structure within the country. Our findings reveal that the minimum wage significantly reduces income disparities, particularly among formal workers at the lower and upper end of the wage distribution. While wage gaps below the median wage decline, those above it experience a slower growth rate, ultimately leading to wage convergence. Notably, this effect is more pronounced during macroeconomic instability from 2016 to 2022, compared with the relatively stable period of 2004-15. Moreover, the outcomes differ depending on individual attributes like gender, age, education, and other relevant factors. Furthermore, we observe tentative evidence of a lighthouse effect to some degree: the minimum wage seems to exert an equalizing influence on the wage structure of workers in the informal sector beyond a certain percentile.
Keywords: LABOR-MARKET EVIDENCE; INEQUALITY; EMPLOYMENT; TURKEY; Business & Economics